Extending the Busines Rules Diagram Method to Web Based System Design - Johnstone, Michael; McDermid, Donald; Venable, John (We-B Centre, School of Management, Edith Cowan University, 2003)
This paper describes two action research studies that focused on evaluating the use of an information system development (ISD) method that was extended for the development of web-based systems that support business-to-consumer electronic commerce (B2C EC). A conventional ISD method (the Business Rules Diagram or BRD method) was extended to support the design of processing and navigation for web-based systems. The paper describes the rationale and the extensions. The two studies showed that the participating development teams were able to successfully use the extended BRD method to elicit, analyse, and specify the detailed processing and navigation for two web-based B2C EC systems.